The celebration of the migrants virgin, identity constructions among bolivians and santafesinos in the agricultural fields located in the city Santa Fe, Argentina - Serafino, María Alicia (Sociedad y Economía, 2010)
The purpose of this paper is to present, theoretically, one of the many religious festivities preformed by Bolivian immigrants in our country. We will situate this paper in the city of Santa Fe and more concretely in Ángel Gallardo. During the 1960 ́s a number of Bolivian families from the region of Tarija settled in the area in search of work. Over time these immigrants, motivated by a priest of the town, began to celebrate the Feast of the Virgin of Chaguaya. Since that time, this Feast is venerated not only by the Bolivian immigrants but by the locals as well, as they have appropriated the Feast and have reassigned the mystical characteristic of the Virgin according to their own values. Through our analysis of this Feast we will try to explain the relationship between Bolivian immigrants and the local inhabitants, whose ties go beyond this religious feast and are also dependent on work, economic and cultural relations. In accordance with current thought related to cultural diversity we will analyze identity forms that are expressed in the celebration of the Virgin of the migrants.